Durkheim and the Jews of France - Strenski, Ivan (Chicago studies in the history of Judaism., 1997)
Ivan Strenski debunks the common notion that there is anything "essentially" Jewish in Durkheim's work. Seeking the Durkheim inside the real world of Jews in France rather than the imagined Jewishness inside Durkheim himself, Strenski adopts a Durkheimian approach to understanding Durkheim's thought. In so doing he shows for the first time that Durkheim's sociology (especially his sociology of religion) took form in relation to the Jewish intellectual life of late nineteenth- and early twentieth-century France. Strenski begins each chapter by weighing particular claims (some anti-Sem.